Oncolytic Virotherapy as Emerging Immunotherapeutic Modality: Potential of Parvovirus H-1 - Moehler, Markus; Goepfert, Katrin; Heinrich, Bernd; Breitbach, Caroline J.; Delic, Maike; Galle, Peter Robert; Rommelaere, Jean (Frontiers in Oncology, 2014)
Human tumors develop multiple strategies to evade recognition and efficient suppression by the immune system. Therefore, a variety of immunotherapeutic strategies have been developed to reactivate and reorganize the human immune system. The recent development of new antibodies against immune check points may help to overcome the immune silencing induced by human tumors. Some of these antibodies have already been approved for treatment of various solid tumor entities. Interestingly, targeting antibodies may be combined with standard chemotherapy or radiation protocols. Furthermore, recent evidence indicates that intratumoral (it) or intravenous (iv) injections of replicative oncolytic viruses such as herpes simplex-, pox-, parvo- or adenoviruses may also reactivate the human immune system. By generating tumor cell lysates in situ, oncolytic viruses overcome cellular tumor resistance mechanisms and induce immunogenic tumor cell death resulting in the recognition of newly released tumor antigens.This is in particular the case of the oncolytic parvovirus H-1 (H-1PV) which is able to kill human tumor cells and stimulate an antitumor immune response through increased presentation of tumor-associated antigens, maturation of dendritic cells and release of proinflammatory cytokines. Current research and clinical studies aim to assess the potential of oncolytic virotherapy and its combination with immunotherapeutic agents or conventional treatments to further induce effective antitumoral immune responses.